Transcriptomic and proteomic analyses of Weissella koreensis isolated from kimchi with different growth-limiting temperatures - Hye In Ko; So-Rim Kim; Moeun Lee; Chae-Rim Jeong; Nuri Na; Jong-Bang Eun; Tae-Woon Kim (Food Research International, 2026)

Effects of metal components in PM2.5 derived from pig farm exposure on ovarian function and oocyte quality - Chae Yeon Kim; Geun Hye Park; Chae Rim Kim; Hyeonjin Kim; Ke Huang; Zhibin Liu; Nangwon Yee; Jiaxi Zhang; Doyoon Kim; Lei Ma; Eungyung Kim; Zae Young Ryoo; et al. (Journal of Hazardous Materials, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Polydeoxyribonucleotides isolated from the food fermentation strain Enterococcus faecium mitigate neuroinflammation via MAPK-mediated BMP/SMAD/Wnt regulation under neuro-oxidative stress - Da Hye Song; Yu-Rim Lee; Seung Min Yu; Soo Youn Lee; Sae-Hun Kim; Jeung Hee An (Food Bioscience, 2026)

Thermodynamic evaluation of lithium recovery and freshwater production by sustainable hydrate-based desalination from brine solutions - Sol Geo Lim; Chang Yeop Oh; Hye Rim Choi; Donghyun Moon; Chiho Sung; Sun Ha Kim; Kongtae Ra; Minjun Cha; Ji-Ho Yoon (Desalination, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Experimental and computational insights into sustainable lithium recovery and freshwater production via CO2 hydrate-based desalination - Sol Geo Lim; Donghyun Moon; Chang Yeop Oh; Hye Rim Choi; Chiho Sung; Sun Ha Kim; Kongtae Ra; Minjun Cha; Ji-Ho Yoon (Chemical Engineering Journal, 2025)

Assessing seepage sources of a tailings dump and fractionation of Mo and Zn isotopes - Duk-Min Kim; Dae-Gyu Im; Hye-Lim Kwon; Seong-Taek Yun; Ki-Rim Lee; Mi-Jeong Park; Mi-Sun Park (Science of The Total Environment, 2025)

Dexamethasone nanocrystals-embedded hydroxypropyl methylcellulose hydrogel increases cochlear delivery and attenuates hearing loss following intratympanic injection - Min Young Jeong; Subin Kim; Hye Rim Kim; Jiae Jeon; Seong Su Won; Keum-Jin Yang; Jun Soo Park; In Gyu Yang; Dong Geon Lee; Jin Hyuk Myung; Yoon-Gyoon Kim; Sung Giu Jin; et al. (Carbohydrate Polymers, 2024)

TDOF PID Controller for Enhanced Disturbance Rejection with MS-Constraints for Speed Control of Marine Diesel Engine - Gun-Baek So; Gang-Gyoo Jin; Chan-Ha Lee; Hye-Rim So; Dae-Jeong Kim; Jong-Kap Ahn (Journal of Marine Science and Engineering, 2024)
This study proposes a two-degree-of-freedom PID controller design and tuning method based on a simple pole placement approach to enhance servo and regulatory performance while ensuring the stability of diesel engines. In the modeling of the control target, the actuator is analytically modeled. In contrast, the type of model for the diesel engine is derived analytically, and its parameter estimation uses operational data from naval ships. The proposed controller consists of a PID controller to improve regulatory performance and a set-point filter to enhance servo response. PID controller parameters consist of the parameters of the controlled plant model and a single tuning variable. At the same time, the set-point filter comprises the controller parameters and a single weighting factor. To ensure the robust stability of the controller, the controller parameters are tuned based on the maximum sensitivity. To verify the effectiveness of this study, simulations for the speed control of a diesel engine with inherent nonlinearity were conducted under three scenarios. Performance was quantitatively analyzed using the integral of time-weighted absolute error, 2% settling time, 2% recovery time, specified maximum sensitivity, and maximum peak response value, and was compared with Skogestad’s IMC and Lee’s IMC. Based on evaluation indices, the proposed controller demonstrated superior performance in both servo and regulatory responses compared to the two existing control techniques while ensuring stability.

HEBP2 affects sensitivity to cisplatin and BCNU but not to paclitaxel in MDA-MB-231 breast cancer cells - Hye Rim Kim; Jin-Kyung Hong; Yongsub Kim; Jeong-Yun Choi (Toxicological Research, 2024)

Safety of applying influenza-antigen-coated microneedles to rat skin and the antigen specific immune response in vivo - Taek-Seon Yun; Bomin Song; Yu-Rim Hwang; Minki Jin; Hyeseung Seonwoo; Donki Kim; Hye Won Kim; Byeong Cheol Kim; Daekyung Kim; Boyeong Park; Jeong Yeon Kang; Seung-Ki Baek; et al. (Journal of Pharmaceutical Investigation, 2024)

Numerical analysis of air–water–solid three-phase flow in airlift pump for seabed mining - Un-Ryong Rim; Hye-Ryong Kim; Jong-Guk Ryom; Sung-Hyok Kim (Ocean Engineering, 2023)

Sustainability assessment of hydrochemical and microbiological disturbances in shallow aquifer by thermal utilization - Jaeyeon Kim; Ji-Young Baek; Hye-na Ko; Dugin Kaown; Hae-Rim Oh; Kang-Kun Lee (Groundwater for Sustainable Development, 2023)

Exploring the potential hypothalamic role in mediating cisplatin-induced negative energy balance - Yang Tae Kim; Byong Seo Park; Hye Rim Yang; Seon Yi; Il Seong Nam-Goong; Jae Geun Kim (Chemico-Biological Interactions, 2023)

Estimation of Genetic Parameters and Optimum Breeding Programme Design in Korean Flatfish Breeding Population - Phuong Thanh N. Dinh; Jong-Won Park; Waruni Ekanayake; Yeongkuk Kim; Dooho Lee; Dain Lee; Hyo Sun Jung; Julan Kim; Hye-Rim Yang; Heegun Lee; Sangwon Yoon; Jeong-Ho Lee; et al. (Fishes, 2022)
Olive flounder (Paralichthys olivaceus) is a vital aquaculture species in East Asia. However, few studies that estimate the genetic parameters of this species have been conducted. We estimated the genetic parameters of growth traits and designed an optimum breeding programme for this species. Heritability, genetic and phenotypic correlations, and breeding values were estimated for growth traits: body weight (BW), total length (TL), and condition factor (CF). A linear mixed animal model using the restricted maximum likelihood (REML) algorithm was applied to the statistical analysis of 9 traits (BW, TL, and CF at 11, 18, and 22 months of age) for a total of 54,159 animals from 7 generations. Increases of 13%, 8%, and 6.5% in BW, TL, and CF at the harvest stage were observed, respectively, after 7 generations of selection. The heritabilities of all growth traits were moderate, ranging from 0.35 to 0.46. The phenotypic and genetic correlations between BW and TL were high and positive in all three stages (0.91 and 0.92, 0.91 and 0.93, and 0.88 and 0.91). The estimated breeding values of BW and TL increased over the generations; however, the estimated breeding value of CF fluctuated. The optimum progeny number within full-sib families for an accuracy of 0.632 is suggested to be between 10 and 25. Findings indicated that a considerable response to selection and single-trait selection based on BW would be effective in olive flounder.

Integrated analysis of miRNA and mRNA expression profiles in diabetic mouse kidney treated to Korean Red Ginseng - Hye Rim Park; Seung Eun Lee; Yoojung Yi; Sangji Moon; Hyunkyung Yoon; Chae Won Kang; Jaetaek Kim; Yong Seek Park (Molecular & Cellular Toxicology, 2022)

Anti-bacterial and Anti-biofilm Effects of Equol on Yersinia enterocolitica - Hye-Rim Kim; Mi-Suk Han; Yong-Bin Eom (Indian Journal of Microbiology, 2022)

Jageum-Jung, the herbal pharmaceuticals, inhibits the hepatic fibrogenesis as mediated with TGF-β1/smad signaling - Yu Rim Song; Mi Hee Jang; Boyun Jang; Su Jin Bae; Seon Been Bak; Sung Min Lee; Un-Jung Yun; Ju Hee Lee; Sang Mi Park; Dae Hwa Jung; Bok Suk Sa; Jong Kuk Song; et al. (Molecular & Cellular Toxicology, 2022)

COCH-related autosomal dominant nonsyndromic hearing loss: a phenotype–genotype study - Kyung Seok Oh; Daniel Walls; Sun Young Joo; Jung Ah Kim; Jee Eun Yoo; Young Ik Koh; Da Hye Kim; John Hoon Rim; Hye Ji Choi; Hye-Youn Kim; Seyoung Yu; Richard J. Smith; et al. (Human Genetics, 2022)

Differential genetic diagnoses of adult post-lingual hearing loss according to the audiogram pattern and novel candidate gene evaluation - John Hoon Rim; Byunghwa Noh; Young Ik Koh; Sun Young Joo; Kyung Seok Oh; Kyumin Kim; Jung Ah Kim; Da Hye Kim; Hye-Youn Kim; Jee Eun Yoo; Seung-Tae Lee; Jin Woong Bok; et al. (Human Genetics, 2022)
Ski-slope hearing loss (HL), which refers to increased auditory threshold at high frequencies, is common in adults. However, genetic contributions to this post-lingual HL remain largely unknown. Here, we prospectively investigated deafness-associated and novel candidate genes causing ski-slope HL. We analyzed 192 families with post-lingual HL via gene panel and/or exome sequencing. With an overall molecular diagnostic rate of 35.4% (68/192) in post-lingual HL, ski-slope HL showed a lower diagnostic rate (30.7%) compared with other conditions (40.7%). In patients who showed HL onset before the age of 40, genetic diagnostic probability was significantly lower for ski-slope HL than for other conditions. Further analysis of 51 genetically undiagnosed patients in the ski-slope HL group identified three variants in delta-like ligand 1 ( DLL1 ), a Notch ligand, which presented in vitro gain-of-function effects on Notch downstream signaling. In conclusion, genetic diagnostic rates in post-lingual HL varied according to audiogram patterns with age-of-onset as a confounding factor. DLL1 was identified as a candidate gene causing ski-slope HL.

Detection of 94 compounds related to sexual enhancement including sildenafil, tadalafil, vardenafil and their analogues in various formulations of dietary supplements and food samples using HPLC and LC-MS/MS - Ji Hyun Lee; A. Young Min; Ok Rim Park; Ji Hye Han; Yoon Ji Yang; Hyungil Kim; Sun Young Baek (Food Additives & Contaminants: Part A, 2021)

Effects of Nitrogen, Phosphorus and Potassium Fertilizers on Growth Characteristics of Two Species of Bellflower (Platycodon grandiflorum) - Soo-Jeong Kwon; Hye-Rim Kim; Swapan Kumar Roy; Hyun-Jung Kim; Hee-Ock Boo; Sun-Hee Woo; Hag-Hyun Kim (Journal of Crop Science and Biotechnology, 2019)

Effects of Temperature, Light Intensity and DIF on Growth Characteristics in Platycodon grandiflorum - Soo-Jeong Kwon; Hye-Rim Kim; Swapan Kumar Roy; Hyun-Jung Kim; Hee-Ock Boo; Sun-Hee Woo; Hag-Hyun Kim (Journal of Crop Science and Biotechnology, 2019)

Protective effect of oil extracted from Neophocaena asiaeorientalis against hydgrogen peroxide-induced oxidative stress in HepG2 cells - Hye Ryeong Kim; Ji Eun Kim; Woo Bin Yun; Mi Rim Lee; Jun Young Choi; Jin Ju Park; Bo Ram Song; Hyun Keun Song; Dae Youn Hwang (Fisheries Science, 2019)

Effect of Combined Exposure to EDTA and Zinc Pyrithione on Pyrithione Absorption in Rats - Dong Sik Jung; Guk Hwa Jung; Eun Ho Lee; Hye Ran Park; Ju Hwan Kim; Kyu-Bong Kim; Hak Rim Kim; Hyung Gun Kim (Toxicological Research, 2019)

Profiling of miRNA expression in mice kidney with diabetic nephropathy - Hye Rim Park; Seung Eun Lee; Hyemi Kim; Seeun Jeon; Dongkyo Han; Young-Ho Jin; Jeong-Je Cho; Hyun-Jong Ahn; Cheung-Seog Park; Jongsung Lee; Yong Seek Park (Molecular & Cellular Toxicology, 2018)

Forced expression of CD200 improves the differentiation capability and immunoregulatory functions of mesenchymal stromal cells - Hye Joung Kim; Kyoung-Woon Kim; Yong-Rim Kwon; Bo-Mi Kim; Yoo-Jin Kim (Biotechnology Letters, 2018)

In vivo Acclimatization Responses of Platycodon grandiflorum For. Duplex to Different Soil Types and Environmental Factors - Soo Jeong Kwon; Swapan Kumar Roy; Hye-Rim Kim; Young-Ja Moon; Sun Hee Woo; Hee Ock Boo; Jin-Woog Koo; Hag Hyun Kim (Journal of Crop Science and Biotechnology, 2018)

Effects of Angelica gigas extract on the oral pharmacokinetics of gefitinib in rats - Hye-Rim Kim; Jong-Woo Jeong; Sang Hoon Joo; Tae-Sung Koo (Journal of Pharmaceutical Investigation, 2018)

Protective effects of carbenoxolone, an 11β-HSD1 inhibitor, against chemical induced dry eye syndrome - Yoon-Ju Na; Kyoung-Jin Choi; Sung Bum Park; Hye-Rim Sung; Won Hoon Jung; Hee Youn Kim; Sang Dal Rhee; Ki Young Kim (Apoptosis, 2017)

Effect of crotonaldehyde on the induction of COX-2 expression in human endothelial cells - Seung Eun Lee; Hye Rim Park; Hyemi Kim; Yeoum Choi; Young-Ho Jin; Cheung-Seog Park; Hyun-Jong Ahn; Jeong-Je Cho; Yong Seek Park (Molecular & Cellular Toxicology, 2017)

Effect of crotonaldehyde on the induction of HO-1 expression in A549 cells - Seung Eun Lee; Hye Rim Park; Hong Duck Yun; Hyemi Kim; Young-Ho Jin; Cheung-Seog Park; Hyun-Jong Ahn; Jeong-Je Cho; Yong Seek Park (Molecular & Cellular Toxicology, 2017)

A biology-driven receptor model for daily pollen allergy risk in Korea based on Weibull probability density function - Kyu Rang Kim; Mijin Kim; Ho-Seong Choe; Mae Ja Han; Hye-Rim Lee; Jae-Won Oh; Baek-Jo Kim (International Journal of Biometeorology, 2017)

Phototoxicity Evaluation of Pharmaceutical Substances with a Reactive Oxygen Species Assay Using Ultraviolet A - Yong Sun Lee; Jung-Sun Yi; Hye Rim Lim; Tae Sung Kim; Il Young Ahn; Kyungyuk Ko; JooHwan Kim; Hye-Kyung Park; Soo Jung Sohn; Jong Kwon Lee (Toxicological Research, 2017)

Development of statistical seasonal prediction models of Arctic Sea Ice concentration using CERES absorbed solar radiation - Yoojin Kim; Ha-Rim Kim; Yong-Sang Choi; WonMoo Kim; Hye-Sil Kim (Asia-Pacific Journal of Atmospheric Sciences, 2016)

Enhanced production of resveratrol derivatives in tobacco plants by improving the metabolic flux of intermediates in the phenylpropanoid pathway - Yu Jeong Jeong; Chul Han An; Su Gyeong Woo; Ji Hye Park; Ki-Won Lee; Sang-Hoon Lee; Yeonggil Rim; Hyung Jae Jeong; Young Bae Ryu; Cha Young Kim (Plant Molecular Biology, 2016)

Diagnostic usefulness of the GenoType MTBDR plus assay for detecting drug-resistant tuberculosis using AFB smear-negative specimens with positive TB-PCR result - Young Seok Lee; Hye-Rim Kang; Si-Hyeong Lee; Yunmi Kim; Mi-Yeong Kim; Jeong Hwan Shin; Jae Young Moon; Hyun-Kyung Lee; So Young Park; Eun-Kyung Mo; Yong Bum Park; Soo-Yoon Moon; et al. (Infectious Diseases, 2016)

Pyruvate Kinase M2: A Novel Biomarker for the Early Detection of Acute Kidney Injury - Ji Hyun Cheon; Sun Young Kim; Ji Yeon Son; Ye Rim Kang; Ji Hye An; Ji Hoon Kwon; Ho Sub Song; Aree Moon; Byung Mu Lee; Hyung Sik Kim (Toxicological Research, 2016)

Enhancement of human mesenchymal stem cell differentiation by combination treatment with 5-azacytidine and trichostatin A - Hye Joung Kim; Yong-Rim Kwon; Yu-Jin Bae; Yoo-Jin Kim (Biotechnology Letters, 2016)

Genetic diversity of Staphylococcus equorum isolates from Saeu-jeotgal evaluated by multilocus sequence typing - Do-Won Jeong; Hye-Rim Kim; Jong-Hoon Lee (Antonie van Leeuwenhoek, 2014)

Microarray analysis of gene expression in 3-methylcholanthrene-treated human endothelial cells - Hye Rim Park; Hana Yang; Gun-Dong Kim; Gun Woo Son; Yong Seek Park (Molecular & Cellular Toxicology, 2014)

A proposal to unify two subspecies of Staphylococcus equorum: Staphylococcus equorum subsp. equorum and Staphylococcus equorum subsp. linens - Do-Won Jeong; Hye-Rim Kim; Seulhwa Han; Che Ok Jeon; Jong-Hoon Lee (Antonie van Leeuwenhoek, 2013)

Time-sequential modulation in expression of growth factors from platelet-rich plasma (PRP) on the chondrocyte cultures - Se-Il Park; Hye-Rim Lee; Sukyoung Kim; Myun-Whan Ahn; Sun Hee Do (Molecular and Cellular Biochemistry, 2012)

Purification and Anticoagulant Activity of a Fucoidan from Korean Undaria pinnatifida Sporophyll - Woo-Jung Kim; Sung-Min Kim; Hyun-Guell Kim; Hye-Rim Oh; Kyung-Bok Lee; Yoo-Kyung Lee; Yong-Il Park (Algae, 2007)